P.016 Hypertensive disorders in pregnancy are associated with future development of vascular dementia: A systematic review and meta-analysis. (November 2021) - Switzer, A; Smith, EE; Ganesh, A
Abstract : Background: We aimed to evaluate the association between hypertensive disorders in pregnancy (HDP) and future risk of cognitive impairment and dementia. Methods: Systematic searches were performed in MEDLINE and EMBASE up to April 27 th, 2020. Exposure of interest included the different types of HDP. Outcomes of interest included dementia incidence, dementia subtype, and cognitive testing. Results: On qualitative review, 4/9 studies showed impaired memory, visual motor processing speed, executive function, and verbal testing in previously preeclamptic women. 2/4 studies showed impaired visual motor processing and subjective cognitive complaints in previously eclamptic women. Six cohort studies involving >2.6 million women were included in the meta-analysis. Pooled hazard ratios (aHR) with 95% confidence intervals were generally adjusted for age at delivery ethnicity, and vascular risk factors. Women with a history of gestational hypertension were more likely to develop vascular dementia (aHR 2.02 [1.45-2.83], I 2 :0%), but not Alzheimer disease (1.24 [0.93-1.66], single-study). Women with a history of preeclampsia were also more likely to develop vascular dementia (2.17 [1.20-3.91], I 2 :61.1%), but not Alzheimer dementia (1.19 [0.83-1.69], I 2 :69.9%). Conclusions: Whereas studies of neuropsychological testing in previously preeclamptic and eclamptic women have been heterogeneous, a history of HDP is associated with developing vascular dementia in later life.